2020
DOI: 10.3390/s20071896
|View full text |Cite
|
Sign up to set email alerts
|

On Image Fusion of Ground Surface Vibration for Mapping and Locating Underground Pipeline Leakage: An Experimental Investigation

Abstract: This paper is concerned with imaging techniques for mapping and locating underground pipeline leakage. Ground surface vibrations induced by the propagating axisymmetric wave can be measured by an array of acoustic/vibration sensors, with the extraction of magnitude information used to determine the position of leak source. A method of connected graph traversal is incorporated into the vibroacoustic technique to obtain the spatial image with better accuracy compared to the conventional magnitude contour plot. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The data was then processed using machine learning techniques to obtain a real time 3D map to infer the location of the buried pipe. More recently, Yan et al [17] investigated an imaging fusion technique based on connected graph transversal that provided a better spatial image of the amplitude information to determine the position of the leak source. Experimental results showed that the proposed model gives better magnitude contour plots when image fusion is applied.…”
Section: Introductionmentioning
confidence: 99%
“…The data was then processed using machine learning techniques to obtain a real time 3D map to infer the location of the buried pipe. More recently, Yan et al [17] investigated an imaging fusion technique based on connected graph transversal that provided a better spatial image of the amplitude information to determine the position of the leak source. Experimental results showed that the proposed model gives better magnitude contour plots when image fusion is applied.…”
Section: Introductionmentioning
confidence: 99%